Contrasting responses of generalized/specialized mistletoe-host interactions under climate change. Issue 3 (3rd July 2018) - Ornelas, Juan Francisco; Licona-Vera, Yuyini; Ortiz-Rodriguez, Andrés E.
ABSTRACT: Considering that parasitic plant distributions are constrained by host availability, we measure the effects of adding information of host distributions to predict distributions of mistletoes under climate change using ecological niche modeling (ENM). We contrasted ecological niche models of two Psittacanthus mistletoe species, P. schiedeanus, a host-generalist species inhabiting cloud forests, and P. sonorae, a Bursera -specialist restricted to the Sonoran Desert. Mistletoe models that use only climate variables were contrasted with models that also take into account biotic interactions (i.e., host) to evaluate the potential effects that future climatic conditions have on the distributions of these mistletoe-host interactions. Current potential distributions of both mistletoe species were affected by environmental conditions under future climate change scenarios. However, future projected distributions differed between mistletoe species when including host interactions, with improved accuracy models for P. schiedeanus . Our results are consistent with previous studies showing that biotic interactions can be important in structuring species distributions at regional scales.